PHRASEOLOGICAL REPRESENTATION OF HUMAN EMOTIONS IN ENGLISH AND KARAKALPAK LANGUAGES - Askarova U.D.; D.T.Xadjieva (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Summary: The expression of human emotions plays an important role in language and reflects the cultural and psychological characteristics of a nation. Phraseological units are one of the most effective linguistic means used to convey emotions, feelings, and attitudes in speech. The main aim of the research is to study the field of phraseology, which mainly includes human emotions in the English and Karakalpak languages. The present study discusses how English phraseological units expressing human emotions are formed, their structures, and the similarities and differences between these phrases and their equivalents in the Karakalpak language. The research is based on comparative semantic, and linguocultural methods of analysis. As a result of the study, it was found that emotions such as happiness are commonly expressed in both languages, but its figurative meanings and cultural differences vary.